Molecular Phylogenetics of Six Dragonfly Species (Odonata: Anisoptera: Libellulidae) of Udaipur Region (Rajasthan) - Rawal Deepak,; Dhaked Jaynesh,; Suthar Yamini, (The Bioscan, 2025)
In current study, mitochondrial COI gene sequencing of six species of dragonflies (Anisoptera: Libellulidae) collected from Udai Sagar lake of Udaipur region was done using Sanger sequencing protocol. All six reported species shows 100% similarity to the NCBI Genbank database. Molecular phylogenesis was done using BLAST (Basic Local Alignment Search Tool). All six Sequences were submitted to Genbank, which would be useful to identify dragonflies in future studies. This study provides phylogeny trees and idea of evolutionary relationship of six dragonfly species.